A demethylation deficient isoform of the lysine demethylase KDM2A interacts with pericentromeric heterochromatin in an HP1a-dependent manner. (3rd September 2017) - Lađinović, Dijana; Novotná, Jitka; Jakšová, Soňa; Raška, Ivan; Vacík, Tomáš
ABSTRACT: Histone modifications have a profound impact on the chromatin structure and gene expression and their correct establishment and recognition is essential for correct cell functioning. Malfunction of histone modifying proteins is associated with developmental defects and diseases and detailed characterization of these proteins is therefore very important. The lysine specific demethylase KDM2A is a CpG island binding protein that has been studied predominantly for its ability to regulate CpG island-associated gene promoters by demethylating their H3K36me2. However, very little attention has been paid to the alternative KDM2A isoform that lacks the N-terminal demethylation domain, KDM2A-SF. Here we characterized KDM2A-SF more in detail and we found that, unlike the canonical full length KDM2A-LF isoform, KDM2A-SF forms distinct nuclear heterochromatic bodies in an HP1a dependent manner. Our chromatin immunoprecipitation experiments further showed that KDM2A binds to transcriptionally silent pericentromeric regions that exhibit high levels of H3K36me2. H3K36me2 is the substrate of the KDM2A demethylation activity and the high levels of this histone modification in the KDM2A-bound pericentromeric regions imply that these regions are occupied by the demethylation deficient KDM2A-SF isoform.